The Less I Know The Better? A Model of Rational Attention and Experimentation (2019)
This paper explores the binary choice of an agent who must allocate her attention to noisy information obtained from costly experimentation to improve her knowledge in a context of uncertainty.We model a two period-lived agent who must decide whether to invest or not in each period. Initial experimentation (investing) enables access to noisy information about the state of nature, which can be refined by paying attention. We find that there is no case for rational inattention. The agent internalizes the fact that information is costly and thus cannot be wasted. Hence, when information is available, attention is a rational action. Moreover, initial experimentation is driven by an endogenous cutoff strategy: the prior beliefs and the cost of attention determine the extent to which information is valuable. Finally, an important finding is that limited attention has no effect on the initial experimentation amount because it never worsens the quality of information. Experimentation is understood as paying for information and therefore the agent pays the lowest price regardless of the quality of information (perfectly informative or noisy).